Object oriented (dynamic) programming: Replication, innovation and "structural" estimation - Christopher Ferrall (Queen's University, Department of Economics, 2020)
This paper discusses how to design, solve and estimate dynamic programming models using the open source package niqlow. Reasons are given for why such a package has not appeared earlier and why the object-oriented approach followed by niqlow seems essential. An example is followed that starts with basic coding then expands the model and applies different solution methods to finally estimate parameters from data. Using niqlow to organize the empirical DP literature may support new research better than traditional surveys. Replication of results in several published papers validate niqlow, but it also raises doubt that complex models solved with purpose-built code can ever be independently verified.
Keywords: C63; C51; C54; 330; Dynamic Programming; Computational Methods; Replication Studies